The Effect of Thai Traditional Play Program on Speed and Agility in Male Students in the Upper Primary School - Thonglong, Thanumporn; Bussamongkhon, Piangpen (Trends in Sciences, 2022)
The purpose of the research was to study and compare the effect of Thai Traditional Play program on the speed and agility of Upper primary school male students. Group samples consisted of 32 male students from Chumchonsampraw School in Udonthani province. The test group (N = 16) was trained with both the Thai Traditional Play program and physical education activity and the control group was trained with physical education activity only. The training 60 min per day, 3 days per week, for 8 weeks. A personal questionnaire was collected and a speed test by using running 50 m and an agility test by using running a zig-zag course. All parameters were measured baseline, at week 4 and 8, respectively. The data were analyzed by using percentage, mean, standard deviation, t-test and One-way analysis of variance with repeated measure. Scheffe was compared at the statistical significance level at p < 0.05. The results showed that the speed and agility of the experimental group before, after the 4th and after the eight weeks were found to be significantly at 0.05 level. But control group found not significantly at 0.05 level. This research suggests that Thai Traditional Play program could increase speed and agility of male students in the Upper primary school. HIGHLIGHTS Thai Traditional play is an activity based on running skills. Walking skills and mobility Thai Traditional play is an exercise because while playing, the child moves the body and every muscle, thus affecting the development of speed and agility Speed ​​and agility are basic skills that elementary school students need to be trained in to have basic movements appropriate for their age GRAPHICAL ABSTRACT